Mature Sunflower Inflorescences Face Geographical East to Maximize Absorbed Light Energy: Orientation of Helianthus annuus Heads Studied by Drone Photography - Takács, Péter; Kovács, Zoltán; Száz, Dénes; Egri, Ádám; Bernáth, Balázs; Slíz-Balogh, Judit; Nagy-Czirok, Magdolna; Lengyel, Zsigmond; Horváth, Gábor (Frontiers in Plant Science, 2022)
Mature sunflower (Helianthus annuus) inflorescences, which no longer follow the Sun, face the eastern celestial hemisphere. Whether they orient toward the azimuth of local sunrise or the geographical east? It was recently shown that they absorb maximum light energy if they face almost exactly the geographical east, and afternoons are usually cloudier than mornings. However, the exact average and standard deviation (SD) of the azimuth angle of the normal vector of mature sunflower inflorescences have never been measured on numerous individuals. It is imaginable that they prefer the direction of sunrise rather than that of the geographical east. To decide between these two photobiological possibilities, we photographed mature inflorescences of 14 sunflower plantations using a drone and determined the average and SD of the azimuth angle of the normal vector of 2,800 sunflower heads. We found that the average azimuth αinflorescence = 89.5° ± 42.8° (measured clockwise from the geographical north) of inflorescences practically coincided with the geographical eastern direction (αeast = 90°) instead of the azimuth of local sunrise αsunrise = 56.14° – 57.55°. Although the SD of the orientation of individual inflorescences was large (± 42.8°), our finding experimentally corroborated the earlier theoretical prediction that the energetically ideal azimuth of sunflower inflorescences is east, if mornings are usually less cloudy than afternoons, which is typical for the domestication region of H. annuus. However, the average orientation of inflorescences of two plantations in hilly landscapes more or less differed from that of the majority of plantations in plane landscapes. The reason for this deviation may be that the illumination conditions in hilly sites more or less differed from those in plane landscapes. Furthermore, in a plantation, we observed a group of south-facing inflorescences that were in shadow for about 5 h both after sunrise and before sunset. This southern orientation can be explained by the southern maximum of total light energy absorbed by the partly shadowed inflorescences during the day, as computed by our software integrating both the diffuse skylight and the direct sunlight received by sunflower inflorescences.